HIV-1–Related Cardiovascular Disease Is Associated With Chronic Inflammation, Frequent Pericardial Effusions, and Probable Myocardial Edema. (March 2016) - Ntusi, Ntobeko; O'Dwyer, Eoin; Dorrell, Lucy; Wainwright, Emma; Piechnik, Stefan; Clutton, Genevieve; Hancock, Gemma; Ferreira, Vanessa; Cox, Pete; Badri, Motasim; Karamitsos, Theodoros; Emmanuel, Sam; et al.
Abstract : Background—: Patients with treated HIV infection have clear survival benefits although with increased cardiac morbidity and mortality. Mechanisms of heart disease may be partly related to untreated chronic inflammation. Cardiovascular magnetic resonance imaging allows a comprehensive assessment of myocardial structure, function, and tissue characterization. We investigated, using cardiovascular magnetic resonance, subclinical inflammation and myocardial disease in asymptomatic HIV-infected individuals. Methods and Results—: Myocardial structure and function were assessed using cardiovascular magnetic resonance at 1.5-T in treated HIV-infected individuals without known cardiovascular disease (n=103; mean age, 45±10 years) compared with healthy controls (n=92; mean age, 44±10 years). Assessments included left ventricular volumes, ejection fraction, strain, regional systolic, diastolic function, native T1 mapping, edema, and gadolinium enhancement. Compared with controls, subjects with HIV infection had 6% lower left ventricular ejection fraction ( P <0.001), 7% higher myocardial mass ( P =0.02), 29% lower peak diastolic strain rate ( P <0.001), 4% higher short-tau inversion recovery values ( P =0.02), and higher native T1 values (969 versus 956 ms in controls; P =0.01). Pericardial effusions and myocardial fibrosis were 3 and 4× more common, respectively, in subjects with HIV infection (both P <0.001). Conclusions—: Treated HIV infection is associated with changes in myocardial structure and function in addition to higher rates of subclinical myocardial edema and fibrosis and frequent pericardial effusions. Chronic systemic inflammation in HIV, which involves the myocardium and pericardium, may explain the high rate of myocardial fibrosis and increased cardiac dysfunction in people living with HIV.